The Effect of Continuous Light on Growth and Muscle-Specific Gene Expression in Atlantic Salmon (Salmo salar L.) Yearlings - Natalia S. Shulgina; Maria V. Churova; Svetlana A. Murzina; Marina Yu. Krupnova; Nina N. Nemova (Life, 2021)
Photoperiod is associated to phenotypic plasticity of somatic growth in several teleost species, however, the molecular mechanisms underlying this phenomenon are currently unknown. The effect of a continuous lighting (LD 24:0), compared with the usual hatchery lighting (HL) regime, on the growth rate and gene expression of myogenic regulatory factors (MRFs: MyoD1 paralogs, Myf5, and MyoG) myosin heavy chain (MyHC), and MSTN paralogs in the white muscles of hatchery-reared Atlantic salmon yearlings was evaluated over a 6-month period (May to October). The levels of gene expression were determined using real-time PCR. Continuous lighting was shown to have a positive effect on weight gain. MyHC, MyoD1c, MyoD1b, and MSTN1a/b mRNA expression was influenced by the light regime applied. In all the studied groups, a significant positive correlation was observed between the expression levels of MRFs and MSTN paralogs throughout the experiment. The study demonstrated seasonal patterns regarding the simultaneous expression of several MRFs. MyoD1a, MyoG, and MyHC mRNA expression levels were elevated in the mid-October, but MyoD1b/c, and Myf5 mRNA levels decreased by the end of this month. In general, the findings showed that constant lighting affected the regulatory mechanisms of muscle growth processes in salmon.